The influence of leaf anatomy on the internal light environment and photosynthetic electron transport rate exploration with a new leaf ray tracing model - Xiao, Yi (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.